2016
DOI: 10.1002/anie.201600275
|View full text |Cite
|
Sign up to set email alerts
|

Stability of B12(CN)122−: Implications for Lithium and Magnesium Ion Batteries

Abstract: Multiply charged negative ions are seldom stable in the gas phase. Electrostatic repulsion leads either to autodetachment of electrons or fragmentation of the parent ion. With a binding energy of the second electron at 0.9 eV, B12 H12 (2-) is a classic example of a stable dianion. It is shown here that ligand substitution can lead to unusually stable multiply charged anions. For example, dodecacyanododecaborate, B12 (CN)12 (2-) , created by substituting H by CN is found to be highly stable with the second elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
84
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 32 publications
2
84
0
1
Order By: Relevance
“…Its anion is formed by a carborane cage surrounded with fluorine atoms and shows superhalogenic behavior. A similar structure with cyano groups, B 12 (CN) 12 2− , was suggested as a highly stable dianion with second electron bound by 5.3 eV …”
Section: Introductionmentioning
confidence: 84%
“…Its anion is formed by a carborane cage surrounded with fluorine atoms and shows superhalogenic behavior. A similar structure with cyano groups, B 12 (CN) 12 2− , was suggested as a highly stable dianion with second electron bound by 5.3 eV …”
Section: Introductionmentioning
confidence: 84%
“…Instead of using only the octet rule,w eu sed multiple electron counting rules simultaneously;n amely,t he octet and Wade-Mingos rules. B 12 [11] showed that B 12 (CN) 12 2À is more stable than its monoanion and it takes 5.3 eV to eject the second electron. [10] According to the Wade-Mingos rule,( n + 1) pairs of electrons are required to stabilize aborane cage where n is the number of vertices in the boron polyhedron.…”
Section: àmentioning
confidence: 99%
“…Here E is the total energy corresponding to the ground-state structure.T he FEA, SEA, and TEA for BeB 11 is strongly stable against its dianion, while the previously studied trianion B(C 3 O 2 ) 3 3À was thermodynamically unstable by À0.40 eV. [7] To validate our numerical method, we computed the structure and energetics of B(C 3 O 2 ) 3 3À using the same level of theory as used for the study of BeB 11 (CN) 12 3À (Supporting Information, Text 1).…”
Section: àmentioning
confidence: 99%
“…The role of substituents in enhancing the stability of multiply charged species in the gas phase was recently studied by substituting H atoms in B 12 H 12 2− by CN moieties. The resulting B 12 (CN) 12 2− cluster was found to be unusually stable with the second electron bound by 5.3 eV, which is almost six times larger than that in the B 12 H 12 2− dianion . The power of substituent engineering was further demonstrated when a B atom in the cage was replaced by a C atom, to form CB 11 (CN) 12 2− .…”
Section: Introductionmentioning
confidence: 95%